Servant Leadership: Inspiring Followers Towards Good Governance in Madrasah - Arifandi, Agus; Khusnuridlo, Khusnuridlo; Mu’is, Abd; Angkananon, Chumphon (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research focuses on exploring the practice of servant leadership in the context of Islamic education in Indonesia. The main objective is to understand how servant leadership practices are applied in various Islamic educational institutions and evaluate their impact on teacher welfare, school performance, and student learning outcomes. The research method used is a qualitative approach with data collection through in-depth interviews with principals, teachers, and staff in various Islamic educational institutions in several regions of Indonesia. Data analysis used a thematic approach to identify critical patterns and findings surrounding servant leadership practices. The results showed that servant leadership practices in Islamic educational environments contributed positively to teacher welfare, school performance, and student learning outcomes. This research implies that servant leadership development can effectively improve the quality of Islamic education in Indonesia. This underscores the importance of service-oriented and inclusive leadership development in Islamic religious education and provides a foundation for developing leadership training programs for future educational leaders.